Rwanda : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about compilation and dissemination of government finance statistics (GFS) in Rwanda. The mission reviewed the roadmap of the interagency GFS technical working group, the structure of the public sector, the GFS compilation process, and the conversion of source data to standard fiscal tables consistent with international standards. The mission fully endorsed the authorities' work program going forward, and agreed that the step-by-step approach starting with producing solid and credible budgetary central government data. The mission cautioned that increasing frequency and expanding coverage of fiscal reports to include the local government sector and, eventually, the extrabudgetary units, will need to be an iterative process requiring continued determined efforts.